Sensation-Seeking and Impulsivity as Predictors of Reactive and Proactive Aggression in Adolescents - Pérez Fuentes, María Del Carmen; Molero Jurado, Maria del Mar; Carrión Martínez, José J.; Mercader Rubio, Isabel; Gázquez, José J. (Frontiers in Psychology, 2016)
In adolescence, such matters as substance use and impulsiveness may give rise to problematic behavior repertoires. This study was therefore done to analyze the predictive value of sensation-seeking and impulsiveness dimensions related to the functions of aggression (reactive/proactive) and types of expression (physical/relational). A total of 822 high school students in Almeria (Spain) aged 13 to 18, were administered the Sensation-Seeking Scale, the State Impulsiveness Scale and Peer Conflict Scale. The results show the existence of a positive correlation of the majority of factors analyzed, both in impulsiveness and sensation-seeking, with respect to the different types of aggression. Furthermore, aggressive behavior is explained by the combination of a sensation-seeking factor (Disinhibition) and two impulsiveness factors (Gratification and Automatism). This study shows the need to analyze aggression as a multidimensional construct.